VIOLÊNCIA CONTRA A MULHER - CRIME PASSIONAL CONTRA A MULHER - Abrantes, Edjânia Maria; Santos, Elisabete Paes dos; Francisco, Kérid; Souza, Liliane Kelly de; Tavares, Magda Manoela Trevisan; Cunha, Maria Gecilene Alves Mendes da; Bezerra, Luiz Carlos Leandro; Macena, Lincoln Villas Boas (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntregra.